Pengaruh Good Corporate Governance (GCG), Gaya Kepemimpinan Dan Etika Kerja Islam Terhadap Kinerja Karyawan Dengan Motivasi Kerja Sebagai Variabel Intervening Studi Pada UMKM Singkong Keju D-9 Salatiga - Amalya, Rizqi; Setiawan, Ananda (Eastasouth Institute, 2024)
The purpose of this study is to analyze the relationship between good corporate governance, leadership style, and Islamic work ethics through work motivation on the performance of Cassava Cheese D-9 Salatiga employees. using quantitative methods, the object of research taken was employees of Cassava Cheese D-9 Salatiga with a total of 50 respondents and processed using SPSS Version 20. Research findings show that work motivation is not able to influence employee performance, but corporate governance, leadership style, and Islamic work ethics are able to influence employee performance, whereas. GCG, leadership style, and Islamic work ethics are not able to influence work motivation. Corporate governance (GCG), leadership style, and Islamic work ethics influence employee performance through work motivation. This research is intended for academics and companies as information, reference, and evaluation related to employee performance.